Determination of Minimum Sample Size Requirement for Multiple Linear Regression and Analysis of Covariance: Considering to get close approximation of the estimates with the parameters in a population - Mohamad Adam Bujang; Nadiah Sa’at; Tg Mohd Ikhwan Tg Abu Bakar Sidik (Epidemiology, Biostatistics and Public Health)
Background: MLR and ANCOVA are common statistical techniques and are used for both experimental and non-experimental studies. However, both types of study designs may require different basis of sample size requirement. Therefore, this study aims to proposed sample size guidelines for MLR and ANCOVA for both experimental and non-experimental studies.